Learning Design in the Time of COVID-19: The Digital Learning Design Unit Story - Orna Farrell (Open Praxis, 2022)
Learning designers became the “first responders” during the great onlining due to the Covid-19 pandemic. In this innovative practice article, we share the experiences of a team of digital learning designers created to support the university community’s pivot online. This project adopts a case study methodology. The case study of the Digital Learning Design Unit (DLDU) described in this article offers an examplar of learning design and the work of learning designers during the time of Covid-19. Findings from this case study indicate that a demand led professional learning approach can be very effective at encouraging staff engagement with learning design; a rapid learning design intervention can provide just in time support for colleagues during a time of crisis; time and digital competencies are essential to build staff competence and confidence with online pedagogy and learning design approaches. In this case study, the pandemic prompted a strategic approach to learning design for online, blended and hybrid education. This strategic approach began as a temporary proactive measure to keep teaching and learning going but has now been cemented into a permanent strategy for online blended and hybrid education at our institution which will continue in the post pandemic environment.